Balancing task focus and relationship building: asking sleepy patients about traffic risk in treatment initiation consultations. Issue 4 (24th April 2017) - Iversen, Clara; Broström, Anders; Ulander, Martin
Abstract : Background: The use of traffic risk assessment questions is an understudied area in nursing research. Obstructive sleep apnoea is associated with an increased risk of traffic accidents. Therefore, traffic safety authorities demand adherent continuous positive airway pressure use. Nurses act as coaches to achieve treatment adherence, but they are also obliged to act as state agents by prohibiting obstructive sleep apnoea patients from drowsy driving. Objective: To examine how nurses and obstructive sleep apnoea patients manage traffic risk assessment questions in the relation‐building context of treatment initiation consultations. Methods: To study, in detail, the actual practice of risk assessment, we used conversation analysis of 19 video‐recorded initial treatment consultations with nurses and recently diagnosed obstructive sleep apnoea patients. Ethics: The study received ethical approval from the Central Ethical Review Board in Linköping (registration number 214/231‐32) and follows the ethical guidelines for qualitative research. Results: Patients influence how nurses phrase questions about traffic risk by taking a stance to daytime sleepiness prior to the risk question. Nurses ask traffic risk questions in a way that assumes that driving is unproblematic if patients have not previously indicated problems. It may pose a significant problem when nurses, by accepting patients' prior stance when asking about traffic risk, orient to relationship building rather than task focus. Conclusion: To clarify the difference between their two potentially conflicting roles, nurses need to refer to existing laws and official guidelines when they raise the issue of risk in treatment initiation consultations. Nurses should also ask risk assessment questions in a problem‐oriented communicative environment. Traffic risk assessment is sensitive yet important, as obstructive sleep apnoea is a highly prevalent problem causing excessive sleepiness. It is essential to acknowledge nurses' double roles with regard to coaching continuous positive airway pressure treatment and assessing traffic risk.